The policies–inequality feedback and health: the case of globalisation. Issue 9 (3rd May 2009) - De Vogli, R; Gimeno, D; Mistry, R
Abstract : Background: Major research contributions aimed at explaining the association between economic inequality and health have concentrated on the plausibility of the material deprivation and psychosocial factors pathways. However, little work has analysed the reciprocal associations between public policies and inequality and their effect on health. Methods: A conceptual framework was first proposed explaining how the public policies–inequality feedback can influence health outcomes via material deprivation and psychosocial factors. Then, a critical review of the literature was conducted and an analysis of the health effects of the globalisation–inequality feedback as a case study. Results: Different bodies of evidence seem to give support to the hypothesis of a public policies–inequality feedback influencing health-related outcomes. This seems to be particularly true when considering globalisation policies. Since the widespread adoption of the so-called "Washington Consensus", economic inequalities have sharply increased worldwide. The rise in inequality has, in turn, further consolidated the adoption of these policies through an increasing "democratic deficit". The reciprocal effects of globalisation and inequality have produced adverse health outcomes between and within societies through both material deprivation and psychosocial stress. Conclusions: Public policies and economic inequality are inextricably interrelated and can affect health through multiple, indirect, reciprocal pathways.